SARS-CoV-2 variant VUI 202012/01 (B.1.1.7) in a pediatric patient: first case report in Ecuador - Jaime David Acosta España; Adriana Veronica Arnao Noboa; Indira Piedad Villacís Ramos; Rosa Esthela Avila Espinoza; Álvaro Felipe Davalos de Castro (Sociedad Ecuatoriana de Pediatría (Núcleo de Quito), 2021)
Introduction: RNA viruses are known to have a high genetic variability. To date, SARS-CoV-2 has produced several variants that can change the clinical presentation of COVID-19. The first clinical case of variant B.1.1.7 with a critical clinical status in a pediatric patient is presented. It indicates that surveillance of new variants and their relationship to critical cases in pediatric patients are required. Clinical case: A pediatric patient with a history of infantile cerebral palsy, complete severe subcortical atrophy, Lennox−Gastaut syndrome, and recurrent pneumonia. She had a slow evolution requiring intensive therapy for acute respiratory distress syndrome (ARDS) that was related to SARS-CoV-2 variant B 1.1.7. Evolution: Initially, she was treated at a private hospital because she required intensive care due to ARDS, and she was then transferred to a public hospital. She was discharged after 35 days due to a favorable evolution of her infectious etiology. Conclusions: New SARS-CoV-2 variants may show new clinical behaviors. Despite this patient's history, a clinical course towards severe symptoms had not been previously observed in pediatric patients with COVID-19. The severe symptoms could be related to the SARS-CoV-2 variant B.1.1.7 infection in this patient.